On the relationship between oil price, exchange rate and stock market performance in South Africa: Further evidence from time-varying and regime switching approaches - Kazeem Abimbola Sanusi; Forget Mingiri Kapingura (Cogent Economics & Finance)
The study examines the dynamics between oil price, exchange rate, and stock market performance in South Africa using DCC-GARCH, time-varying VAR, and multivariate Markov regime switching models. Monthly data on oil price, exchange rate, and market capitalization as a measure of stock performance from 2003(01) to 2019(7) were employed. The results of DCC-GARCH model show that dynamic conditional correlation among the variable was stable with few exceptionalities. The empirical findings from time-varying VAR show existence of feedbacks from stock market to oil price. Markov regime switching VAR model results show that exchange rate and market capitalization have significant effects on oil price in booming period. The study concludes that stock market performance provides an important policy help in stemming the erratic fluctuations in oil price. Appropriate knowledge of the linkage between oil price, exchange rate and stock market performance in South African economy is important because of her heavy reliance on oil importation. The upward change in oil price has so many overlapping effects on many sectors of the economy in form of increase in cost of goods and services (inflation) and lower standard of living among others. Hike in oil price is believed to also worsen the external value of Rands. This could send some dangerous signals to foreign investors in the stock market, which may undermine the performance of the stock market. Empirical knowledge of this dynamic could assist the policy makers to come up with mitigating policies to reduce the effects of oil price volatility on other economic fundamentals.